Clinical implementation of routine screening for fetal trisomies in the UK NHS: cell‐free DNA test contingent on results from first‐trimester combined test. (26th October 2015) - Gil, M. M.; Revello, R.; Poon, L. C.; Akolekar, R.; Nicolaides, K. H.
Abstract : This article has been selected for Journal Club. Clickhere to view slides and discussion points. ABSTRACT: Objectives: Cell‐free DNA (cfDNA) analysis of maternal blood for detection of trisomies 21, 18 and 13 is superior to other methods of screening but is expensive. One strategy to maximize performance at reduced cost is to offer cfDNA testing contingent on the results of the first‐trimester combined test that is used currently. The objectives of this study were to report the feasibility of implementing such screening, to examine the factors affecting patient decisions concerning their options for screening and decisions on the management of affected pregnancies and to report the prenatal diagnosis of fetal trisomies and outcome of affected pregnancies following the introduction of contingent screening. Methods: We examined routine clinical implementation of contingent screening in 11 692 singleton pregnancies in two National Health Service (NHS) hospitals in the UK. Women with a risk ≥ 1 in 100 (high‐risk group) were offered options of invasive testing, cfDNA testing or no further testing, and those with a risk between 1 in 101 and 1 in 2500 (intermediate‐risk group) were offered cfDNA testing or no further testing. The trisomic status of the pregnancies was determined by prenatal or postnatal karyotyping or by examination of the neonates. Results: In the study population of 11 692 pregnancies, there were 47 cases of trisomy 21 and 28 of trisomies 18 or 13. Screening with the combined test followed by invasive testing for all patients in the high‐risk group potentially could have detected 87% of trisomy 21 and 93% of trisomies 18 or 13, at a false‐positive rate of 3.4%; the respective values for cfDNA testing in the high‐ and intermediate‐risk groups were 98%, 82% and 0.25%. However, in the high‐risk group, 38% of women chose invasive testing and 60% chose cfDNA testing; in the intermediate‐risk group 92% opted for cfDNA testing. A prenatal diagnosis was made in 43 (91.5%) pregnancies with trisomy 21 and all pregnancies with trisomies 18 or 13. In many affected pregnancies the parents chose to avoid testing or termination and 32% of pregnancies with trisomy 21 resulted in live births. Conclusions: Screening for fetal trisomies by cfDNA analysis of maternal blood, contingent on the results of the combined test, can be implemented easily in routine clinical practice. In the high‐risk group from the combined test, most but not all women chose cfDNA testing rather than invasive testing. Performance of screening for trisomy 21 was superior by the cfDNA test than by the combined test. However, prenatal detection of trisomies and pregnancy outcome depend not only on performance of screening tests but also on parental choice. Copyright © 2015 ISUOG. Published by John Wiley & Sons Ltd.